Influence of Oxygen Admixture on Plasma Nitrocarburizing Process and Monitoring of an Active Screen Plasma Treatment - Jan Böcker (MDPI AG, 2021)
The effect of a controlled oxygen admixture to a plasma nitrocarburizing process using active screen technology and an active screen made of carbon was investigated to control the carburizing potential within the plasma-assisted process. Laser absorption spectroscopy was used to determine the resulting process gas composition at different levels of oxygen admixture using O2 and CO2, respectively, as well as the long-term trends of the concentration of major reaction products over the duration of a material treatment of ARMCO® iron. The short-term studies of the resulting process gas composition, as a function of oxygen addition to the process feed gases N2 and H2, showed that a stepwise increase in oxygen addition led to the formation of oxygen-containing species, such as CO, CO2, and H2O, and to a significant decrease in the concentrations of hydrocarbons and HCN. Despite increased oxygen concentration within the process gas, no oxygen enrichment was observed in the compound layer of ARMCO® iron; however, the diffusion depth of nitrogen and carbon increased significantly. Increasing the local nitrogen concentration changed the stoichiometry of the ε-Fe3(N,C)1+x phase in the compound layer and opens up additional degrees of freedom for improved process control.